2022
DOI: 10.1021/acs.est.1c06289
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Sources and Fate of NO3 in the Vadose Zone–Groundwater System of a Thousand-Year-Cultivated Region

Abstract: Excess nitrate (NO3 –) loading in terrestrial and aquatic ecosystems can result in critical environmental and health issues. NO3 –-rich groundwater has been recorded in the Guanzhong Plain in the Yellow River Basin of China for over 1000 years. To assess the sources and fate of NO3 – in the vadose zone and groundwater, numerous samples were collected via borehole drilling and field surveys, followed by analysis and stable NO3 – isotope quantification. The results demonstrated that the NO3 – concentration in 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Nitrate (NO 3 − ) from the vadose zone was deposited in the underlying aquifer after GTF, and this behavior became the main way to increase the nitrate concentration in the aquifer. 125,126 The capillary fringe could drive the transportation and reaction of components in both the capillary fringe and GTF; as such, the cycling of dissolved organic carbon and dissolved inorganic nitrogen presented different change trends with the help of the capillary fringe. 127 A field study implied that a nitrate reducer had a high content below the groundwater table and nitrate agents were redistributed during GTF.…”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrate (NO 3 − ) from the vadose zone was deposited in the underlying aquifer after GTF, and this behavior became the main way to increase the nitrate concentration in the aquifer. 125,126 The capillary fringe could drive the transportation and reaction of components in both the capillary fringe and GTF; as such, the cycling of dissolved organic carbon and dissolved inorganic nitrogen presented different change trends with the help of the capillary fringe. 127 A field study implied that a nitrate reducer had a high content below the groundwater table and nitrate agents were redistributed during GTF.…”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%
“…Dynamic variation of the groundwater table plays an important role in regulating nitrogen (N) cycles between unsaturated soil and saturated aquifers (Figure ). Nitrate (NO 3 – ) from the vadose zone was deposited in the underlying aquifer after GTF, and this behavior became the main way to increase the nitrate concentration in the aquifer. , The capillary fringe could drive the transportation and reaction of components in both the capillary fringe and GTF; as such, the cycling of dissolved organic carbon and dissolved inorganic nitrogen presented different change trends with the help of the capillary fringe …”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, groundwater residence time affects groundwater renewability (and thus hydrochemical environment) and the transportation and transformation of NO3 ${{\text{NO}}_{3}}^{-}$ in groundwater (Böhlke & Denver, 1995; Gooddy et al., 2006; Taufiq et al., 2019). These lead to the fact that NO3 ${{\text{NO}}_{3}}^{-}$ in groundwater might not originate from local pollutants or current activities, and even affect the biochemical process of NO3 ${{\text{NO}}_{3}}^{-}$ with changing the redox environment (Niu et al., 2022; Ransom et al., 2016; Yue et al., 2020). For instance, previous studies have stated that groundwater typically exhibited oxygen concentrations of <2 mg/L after long residence time, and NO3 ${{\text{NO}}_{3}}^{-}$ may be attenuated by denitrification (Green et al., 2016; Lindsey et al., 2003; Wolters et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies have stated that groundwater typically exhibited oxygen concentrations of <2 mg/L after long residence time, and NO3 ${{\text{NO}}_{3}}^{-}$ may be attenuated by denitrification (Green et al., 2016; Lindsey et al., 2003; Wolters et al., 2022). Some studies also found that NO3 ${{\text{NO}}_{3}}^{-}$ in groundwater with long residence time may originate from the historically accumulated legacy NO3 ${{\text{NO}}_{3}}^{-}$ stores (Basu et al., 2010; Böhlke & Denver, 1995; Niu et al., 2022; Taufiq et al., 2019; Winter et al., 2021). This explains why NO3 ${{\text{NO}}_{3}}^{-}$ concentration in groundwater may remain high even after reducing fertilizer application in source areas.…”
Section: Introductionmentioning
confidence: 99%